THE OBSTETRIC TACTICS IN ACUTE APPENDICITIS IN PREGNANCY - A. G. Khasanov; F. F. Badretdinova; R. F. Magafurov; Z. R. Shevchenko; A. R. Nurieva; O. C. Mamedova (Акушерство, гинекология и репродукция, 2016)
The results of tocolytic therapy for prolongation pregnancy and delivery in pregnant women with severe appendicitis 45. In the structure of the women operated on appendicitis pregnant amounted to 5.7%. The aim of this study was to optimize obstetric tactics in women with severe appendicitis in different periods of gestation. The core group included 45 women whose pregnancy was complicated by the development of acute appendicitis. A control group consisted of 38 women with normal pregnancies. On the trimestram of gestation, patients were as follows: 14 women in the first trimester of pregnancy; 21-in the second and 10 women in the third trimester of pregnancy. Destructive forms of appendicitis in 29 (64.4%) and pregnant. Application of progestin and β- agonists for prolongation of pregnancy with acute appendicitis allows you to save the pregnancy for most women in the postoperative period. 26 (57.8%) and havewomen pregnancy resulted in urgent, at 7 (15.5%) and women late preterm birth. Artificial termination of pregnancy for medical reasons was 4 patients with destructive appendicitis in the first trimester of pregnancy. In late pregnancy 8 patients performed a caesarean section at the lower end and appendectomy of medial access. Among the women in the control group 29 (76.3 per cent) have pregnancy ended urgent delivery (P<0.05). In the control group, there was a spontaneous miscarriage, women’s 3 x 2 (df=1)-0.02 p=0.8813, yates corrected x 2-0.06 r=0.8058. In small stages of pregnancy complications of appendicitis forms obstetric tactics should be aimed at preserving reproductive functions, rather than on maintaining pregnancy. Given the presence in the arsenal of highly effective antibacterial preparations at term and limited forms of peritonitis may serves as a c-section delivery.